Nature and dependence of variations of water permeability of the rocks of the active water exchange zone on the east of Tatarstan - R. Kh. Musin; R. Z. Musina (Известия высших учебных заведений: Геология и разведка, 2016)
The variations of water permeability of the reservoir rocks with the most productive characteristics for the drinking ground water in the oil regions of Tatarstan are considered. The pore porosity is shown to be responsible for the filter coefficients to 6-10 m /day, whereas the higher values of permeability are determined by fractures porosity. The determining role in the anisotropy of the filtration anisotropy is taken by geomorphological and geological-structural conditions of the territory, and the facial features of the rocks and the depth of their occurrence. On the basis of the established regularities of the behavior of the filtration field, the most probable values of permeability of reservoir rocks for different conditions of their occurrence were calculated.